Социологический анализ спортивной активности населения Украины - Кириленко, О. (Социология: теория, методы, маркетинг, 2007)
The author raises an important question of sport and health sociology, analyzing the results of national research on level, forms, and social factors of sports activity among Ukrainian population. The importance of conducted analysis, as well as necessity to study comprehensively problems of physical training and engagement in sports, is emphasized. For this purpose various empirical methods, especially monitoring survey can be applied.